2015
DOI: 10.1016/j.dsr.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Sinking particle flux in the sea ice zone of the Amundsen Shelf, Antarctica

Abstract: a b s t r a c tWe have examined the flux, biogenic composition, and isotopic values of sinking particles collected by a time-series sediment trap deployed in the sea ice zone (SIZ) of the Amundsen Sea from January 2011 for 1 year. The major portion of the particle flux occurred during the austral summer in January and February when sea ice concentration was reduced to o 60%. Biogenic components, dominated by opal ( $ 78% of the biogenic components), accounted for over 75% of particle flux during this high-flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
(48 reference statements)
2
27
0
Order By: Relevance
“…Kim et al (2014) observed an annual POC flux similar to ours at a site 250 km to the northwest, in the sea ice zone outside the ASP, an area covered by sea ice throughout the year. Primary production in the SIZ region averaged 17 mmol C m −2 d −1 in December 2010 and January 2011 (Lee et al, 2012), about 10% of the values inside the ASP.…”
Section: Other Considerationsmentioning
confidence: 54%
See 3 more Smart Citations
“…Kim et al (2014) observed an annual POC flux similar to ours at a site 250 km to the northwest, in the sea ice zone outside the ASP, an area covered by sea ice throughout the year. Primary production in the SIZ region averaged 17 mmol C m −2 d −1 in December 2010 and January 2011 (Lee et al, 2012), about 10% of the values inside the ASP.…”
Section: Other Considerationsmentioning
confidence: 54%
“…Indeed, ASPIRE observations of high POC inventories and large krill populations associated with marginal sea ice Station 66 on the northern edge of the ASP (Wilson et al, 2015;Yager et al, 2014) may offer insight for the springtime flux we observed the following year. Kim et al (2014) present sediment trap observations overlapping ours in time, but from the zone of persistent 40-100% sea ice cover 250 km northwest of the central ASP (Figure 1). They observed one peak in early 2011, but did not see a second peak at the end of the year.…”
Section: Seasonality and Evolution Of The Annual Flux Eventsmentioning
confidence: 73%
See 2 more Smart Citations
“…Although the export and NCP fractions were typical of other ocean ecosystems (Henson et al, 2012), only about 1% of the export flux leaving the upper 50-100 meters survived to be captured in moored sediment traps at 350-400 meters Kim et al, 2015). Organic degradation in the Amundsen shelf sediment measured by oxygen consumption (aerobic respiration) and sulfate reduction (anaerobic) accounted for only about 1% of the primary production in the surface water (Kim, S.H.…”
Section: La Et Al (This Issue) Conducted Acoustic Analyses On Volume-mentioning
confidence: 99%